Colonização e resistência a antimicrobianos de Staphylococcus spp. em gatos hospitalizados e não hospitalizados de Belo Horizonte, Minas Gerais. - Thayanne Gabryelle Viana de Souza (2024)
The Staphylococcus genus is known for colonizing a wide variety of hosts and is an important member of the oral and cutaneous microbiota of humans and animals. Some species, such as S. aureus, S. pseudintermedius and S. haemolyticus, stand out for acquiring resistance genes, and the isolation of multidrug-resistant strains in infectious conditions in both humans and small animals is increasingly common. In this context, methicillin-resistant staphylococci (MRS), which are resistant to beta-lactam antimicrobials, and commonly also to fluoroquinolones, aminoglycosides and macrolides. However, despite the relevance of this topic in veterinary medicine, not much is known about the species that colonize cats, the susceptibility of these isolates to antimicrobials, as well as the risk factors related to colonization by multidrug-resistant Staphylococcus spp. Therefore, the objective of this study was to isolate and identify bacteria of the Staphylococcus genus that colonize hospitalized and non-hospitalized domestic cats, as well as to analyze their antimicrobial resistance profile. A total of 218 oral and axillary swabs were obtained from 109 cats, 77 of which were not hospitalized and 32 of which were hospitalized at a veterinary clinic in Belo Horizonte, Minas Gerais. After plating on salt mannitol agar, the suggestive colonies were identified by MALDI-ToF or by sequencing of the rpoB and 16S rRNA genes, where necessary. The identity of the S. pseudintermedius isolates was confirmed by PCR of the nuc gene. Antimicrobial susceptibility tests and identification of the mecA gene were carried out on samples resistant to oxacillin/cefoxitin. The isolates identified as methicillin-resistant S. haemolyticus (MRSH) were submitted to the Multilocus Sequence Type (MLST) technique. Eighty-one isolates were obtained from 58 domestic cats (53.2%). S. felis was commonly isolated from non-hospitalized cats (28.1%) and S. pseudintermedius was higher in hospitalized cats (25%). Resistance to penicillin, erythromycin and oxacillin (61.7%, 35.8% and 32%, respectively) were the most frequently observed, while most isolates were sensitive to nitrofurantoin, chloramphenicol and ciprofloxacin (100%, 98.7% and 87.7%, respectively). The majority of multidrug-resistant isolates positive for the mecA gene came from hospitalized cats (21/81 - 26%) (p=0.0388), presenting around three times more chances of isolating such strains, with five being S. pseudintermedius (MRSP) and four S. haemolyticus (MRSH). The MRSH isolates detected in the clinic had the same antimicrobial resistance profile and were classified in the same sequence type (ST3), suggesting clonality. Felines with comorbidities and under antimicrobial use were, respectively, three and 14 times more likely to isolate multidrug-resistant Staphylococcus spp. In conclusion, S. felis is common in the microbiota of non-hospitalized cats and S. pseudintermedius is associated with hospitalized cats. In addition, hospitalization and the use of antimicrobials considerably increase the probability of acquiring multidrug-resistant Staphylococcus spp. in domestic cats, and these factors demonstrate an interference in the colonization dynamics of these animals.